ANALISIS RASIO UNTUK MENILAI KINERJA KEUANGAN PEMERINTAH DAERAH PROVINSI MALUKU TAHUN ANGGARAN 2008-2018 - Nurbaida Nurbaida (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2019)
This study aims to assess the Financial Performance of the Maluku Provincial Government in 2008 - 2018 viewed from: (1) Regional Financial Independence Ratio, (2) PAD Effectiveness Ratio, (3) Dependency Ratio, (4) Fiscal Effort Ratio, and (5) Fiscal Decentralization Ratio. This research is a quantitative descriptive study, by calculating the values in the realization report of the Maluku Province Regional Budget 2008 - 2018. The results of the study during the study period showed that the financial performance of Maluku Province based on the Independence Ratio was in the Poor Criteria, Based on the PAD Effectiveness Ratio Ineffective Criteria, Regional Finance Dependency Ratio is very high dependency on funds originating from the central government, Fiscal Efforts Ratio has Poor Criteria because it has not been able to reach the PAD target, and the Fiscal Decentralization Ratio has a poor criterion. Keywords: Regional Financial Performance, Regional Financial Independence Ratio, PAD Effectiveness Ratio, Dependency Ratio, Fiscal Effort Ratio, and Fiscal Decentralization Ratio.